Domino liver transplantation using livers from patients with familial amyloidotic polyneuropathy - Furtado, AL (2000)
Transplantation of livers from patients with familial amyloidotic polyneuropathy undergoing orthotopic liver transplantation is based on the normal functions of these livers, except for the production of an abnormal protein that causes the disease, which takes more than 20 years to become clinically apparent. Given the shortage of cadaver grafts, domino liver transplantation has the potential to increase the offer to some selected patients. The known experience amounts to little more than 80 cases. Domino liver transplantation has been a safe procedure with all the advantages of living donor grafts. So far, the disease has not shown up in any recipient, including the longest surviving patient (4 years). Particularly in countries where the disease is common, the potential to increase graft offer may be significantly augmented through cooperation between centers and better exploitation of technical possibilities. The combination of split and domino has been reported six times and may provide three to six transplants from only one cadaver graft